Peran Kepuasan Konsumen Sebagai Mediator Pengaruh Persepsi Kualitas Layanan Dan Persepsi Harga Terhadap Loyalitas Konsumen - Nida Arista Ramadhanti; Sulistiono Sulistiono (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to find out if the Role of Consumer Satisfaction as a Mediator Between The Perception of Service Quality and Price Perception positively and significantly affects Consumer Loyalty. The population in this study is GOJEK Online Transportation Service Users In Bogor City with a sample number of 210 people. This research was conducted using SEM (Structural Equation Modelling) analysis using SPSS 23 and LISREL 8.8 Software. The results of this study are as follows: (1) Service Quality Perception has a positive influence and significantly on Consumer Satisfaction as a mediator with a t-Value value of 4.55 > Critical Ratio (CR) value of 1.96. (2) Price Perception has a positive influence and significantly on Consumer Satisfaction as a mediator with a t-Value value of 7.69 > Critical Ratio (CR) value of 1.96. (3) Service Quality Perception has a positive and significant influence on Consumer Loyalty with a t-Value of 2.64 > Critical Ratio (CR) value of 1.96. (4) Price Perception has a positive and significant influence on Consumer Loyalty with a t-Value of 2.13 > a Critical Ratio (CR) value of 1.96. (5) Customer Satisfaction as a mediator has a positive and significant influence on Consumer Loyalty with a t-Value of 4.09 > a Critical Ratio (CR) value of 1.96. (6) Service Quality Perception has a positive and significant influence on Consumer Loyalty through Consumer Satisfaction as a mediator with a t-Value value of 3.33 > Critical Ratio (CR) value of 1.96. (7) Price Perception has a positive and significant influence on Consumer Loyalty through Consumer Satisfaction as a mediator with a t-Value value of 3.93 > a Critical Ratio (CR) value of 1.96.